ANALISIS PERBEDAAN KODE DIAGNOSIS ICD-10 ANTARA RUMAH SAKIT DENGAN VERIFIKATOR BPJS KESEHATAN - Belni Pulpilasari; Sudiro Sudiro; Juliandi Harahap (Universitas Prima Indonesia, 2022)
The accuracy of the diagnosis code is important as a determinant in the financing of health services. The delay in payment of BPJS Health claims can occur if there is a difference in the diagnosis code. This study aims to describe the differences in the ICD 10 diagnosis code between hospitals and BPJS Health Verifiers and the factors that influence them. Qualitative research with data collection techniques through in-depth interviews and documentation studies. The research informants consisted of the main informants as many as 3 Doctors in Charge of Service (DPJP) and the triangulation informants as many as 3 people, namely the Internal Verifier, Coder, and Head of the Medical Record Section. Processing and analyzing data using the content analysis method. The results of the study were 187 claim files experienced delays in payment due to differences in diagnosis codes, no quality audit of diagnosis coding was carried out, no clinical protocol, lack of cooperation between DPJP, coder, and internal verifier, lack of understanding of DPJP, lack of hospital management role involving DPJP in writing the code diagnosis, the absence of hospital policies/SOPs related to writing the ICD 10 diagnosis code, not providing diagnostic coding training. The conclusion of the study is that there are differences in the ICD 10 diagnosis code due to the absence of quality audits for diagnosis coding, clinical protocols, and the role of hospital management which is lacking in preparing policies and training on diagnosis coding causing delays in claim payments.